Science Communication Desperately Needs More Aligned Recommendation Algorithms - Hoang, Lê Nguyên (Frontiers in Communication, 2020)
With 1 billion watch-time hours per day, YouTube now plays a major role in communication. Unfortunately, a large amount of misinformation is produced and widely shared on this platform (Donzelli et al., 2018; Allgaier, 2019; Loeb et al., 2019). In this paper, after providing a brief overview of the creation of science content on YouTube, we particularly emphasize the importance of YouTube's automated recommendations. We then discuss the main challenges of making such recommendations aligned with quality science communication.